Development of Computer-AidedCognitive Training Program for Elderly and Its Effectivenessthrougha 6 Months Group Intervention Study - Otsuka, Tsunehiro; Tanemura, Rumi; Noda, Kazue; Nagao, Toru; Sakai, Hiroshi; Luo, Zhi-Wei (Current Alzheimer Research, 2015)
Since the increasing population of aging, cognitive training is focused as one of the non-pharmacological preventive approach of cognitive decline. Although the accumulation of the knowledge, they hardly reflect to the programs for clinical use. We developed a task set named “Atama-no-dojo,” designed to activate multiple cognitive functions and enhance motivational incentives. The objective of our study is to confirm the effect of our program through a 6 months group intervention program. The intervention program conducted in a day service center for 6 months in the duration of 45 minutes per day, 4 days per month for a total of 25 sessions. Participants worked to the tasks on the screen all together with filling in the answering sheet. Neuropsychological tests, SF36 and GDS were assessed at pre-/post-intervention periods. Participants filled in a questionnaire about impression to the program at the last training session. Fourteen women (82.2±2.9 years old) were analyzed and significant changes were found in the improvement of memory, attention, inhibition, GDS and some items of SF36. All participants recognized the program as fun and wanted to continue. Some of the participants’ positive impressions to the program correlated to cognitive improvement. The improved cognitive functions by 6 months intervention of “Atama-no-dojo” were mainly related to prefrontal cortex and the motivational incentives seemed supported the effect of task contents. We recognized the importance of task difficulty setting and motivational incentives to reduce frustration from working on difficult tasks and enhance the effects of improvement from activating brain function.
Keywords: motivation